Pengaturan Dan Pemenuhan Hak Pendidikan Anak Anak Pengungsi Di Negara Transit Berdasarkan Hukum Internasional - Siahaya, Brian S; Wattimena, Josina Augustina Yvonne; Noya, Ekberth Vallen (Faculty of Law Universitas Pattimura, 2025)
Since the completion of the international convention on refugees (Convention Relating To The Status Of Refugees) in 1951 plus the 1967 protocol (Protocol Relating To The Status Of Refugees), until now Indonesia has not ratified the Convention into a form of legislation due to several obligations that according to the government are still not possible to ratify the convention. This type of research is normative juridical where the research is conducted by collecting primary, secondary and tertiary data obtained using literature studies. The collected data is analyzed qualitatively, the description of which is arranged systematically based on legal disciplines to achieve clarity on the problems to be discussed. The results of this study indicate that transit countries are required to provide protection for children trapped in migration or refugee situations. Article 3: States that every decision taken regarding children must prioritize the best interests of the child. Transit States must ensure that any policies or measures they take do not harm children in their care or custody, Articles 28 and 24 Transit States must ensure children’s access to education and health services, even if they are migrants or refugees. Refugee children have the right to an adequate education, and transit States must provide such access without discrimination, and the 1951 Convention relating to the Status of Refugees and its 1967 Protocol require States not to return individuals who are at risk of harm, including children. In transit States, if a child is at risk of abuse, exploitation or other threats in their country of origin, they should not be returned.